Toll-like receptor-targeted anti-tumor therapies: Advances and challenges - Yang, Yang; Li, Hongyi; Fotopoulou, Christina; Cunnea, Paula; Zhao, Xia (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) are pattern recognition receptors, originally discovered to stimulate innate immune reactions against microbial infection. TLRs also play essential roles in bridging the innate and adaptive immune system, playing multiple roles in inflammation, autoimmune diseases, and cancer. Thanks to the immune stimulatory potential of TLRs, TLR-targeted strategies in cancer treatment have proved to be able to regulate the tumor microenvironment towards tumoricidal phenotypes. Quantities of pre-clinical studies and clinical trials using TLR-targeted strategies in treating cancer have been initiated, with some drugs already becoming part of standard care. Here we review the structure, ligand, signaling pathways, and expression of TLRs; we then provide an overview of the pre-clinical studies and an updated clinical trial watch targeting each TLR in cancer treatment; and finally, we discuss the challenges and prospects of TLR-targeted therapy.